2020
DOI: 10.3390/jcm9113689
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Pretreatment with Pitavastatin on Contrast-Induced Nephropathy in Patients with Renal Dysfunction Undergoing Coronary Procedure: PRINCIPLE-II Randomized Clinical Trial

Abstract: This study aimed to evaluate the efficacy of pitavastatin pretreatment on contrast-induced nephropathy (CIN) in patients with chronic kidney disease (CKD) after a coronary procedure. This was a prospective, randomized, double-blinded, placebo-controlled, multicenter clinical trial. All consecutive 70 patients with CKD (eGFR < 60 mL/min/1.73 m2) were enrolled and randomized into two groups. Group I consisted of patients who were treated with statins (pitavastatin 4 mg/day) for seven days before and three day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Given that preprocedural hydration with saline or bicarbonate has been shown to prevent PC-AKI [34][35][36], restoration of intravascular volume should be achieved before emergency angiography. As anti-inflammatory medications, such as statins, have shown promising results for the prevention of PC-AKI in clinical studies on coronary angiography [37], this potential treatment should be investigated as an adjunct in trauma patients who require an angiography. Urine alkalization is scheduled to be investigated in an upcoming randomized controlled trial and may become an option for PC-AKI prevention in the near future [38].…”
Section: Discussionmentioning
confidence: 99%
“…Given that preprocedural hydration with saline or bicarbonate has been shown to prevent PC-AKI [34][35][36], restoration of intravascular volume should be achieved before emergency angiography. As anti-inflammatory medications, such as statins, have shown promising results for the prevention of PC-AKI in clinical studies on coronary angiography [37], this potential treatment should be investigated as an adjunct in trauma patients who require an angiography. Urine alkalization is scheduled to be investigated in an upcoming randomized controlled trial and may become an option for PC-AKI prevention in the near future [38].…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have shown the nephroprotective efects of statins, including pitavastatin [45][46][47][48][49][50][51], the specifc involvement of the miR-93/PTEN/Akt/mTOR pathway in mediating these efects has not been elucidated in vivo in the context of xenobiotic-induced kidney injury. Our study is the frst to demonstrate that pitavastatin attenuates TAAinduced kidney damage in rats by regulating this essential signaling cascade.…”
Section: Discussionmentioning
confidence: 98%